PENGARUH ORIENTASI PASAR, PEMBELAJARAN ORGANISASI DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA UMKM DI KABUPATEN GRESIK - jurnalpps pps; Agus Irwan Priyono; Nugroho Mardi Wibowo (Prodi Magister Manajemen Universitas Wijaya Putra, 2021)
The purpose of this study was to determine the effect of market orientation, organizational learning and entrepreneurial orientation on the performance of MSMEs in Gresik Regency. The population in this study is MSMEs in Gresik Regency. Using proportional random sampling based on the business sector, after calculating the Slovin formula (sampling error 10%) obtained a sample of 100 SMEs. The analysis used is multiple linear regression. The results and conclusions in this study are market orientation, organizational learning, and entrepreneurial orientation simultaneously have a significant effect on the performance of MSMEs in Gresik district, market orientation has a significant effect on the performance of MSMEs in Gresik district, organizational learning has a significant effect on the performance of MSMEs in Gresik district, orientation entrepreneurship has a significant influence on the performance of MSMEs in Gresik district.